Production Systems to Minimize the Latex Harvesting Cost of Rubber (Hevea brasiliensis) - Soumahin Eric Francis; Adou Bini Yao Christophe; Tonessia Dolou Charlotte; Obouayeba Samuel (European Scientific Journal, ESJ, 2018)
Latex harvesting is the most costly activity in natural rubber production and the shortage of available skill and unstable latex harvester are the main factor affecting in Rubber cultivation and its lead to increase cost of production. Low frequency system (LFT) with the hormonal stimulation is a solution to solve this problem that minimize the cost of latex harvesting. Therefore, a study was conducted for nine years on production systems that minimize the cost of latex harvesting in southwestern Côte d'Ivoire with clones IRCA 130, GT 1 and PB 217 of Hevea brasiliensis. These production systems differ from each other by an increase in tapping frequency, in comparison with the standard tapping (d3) on the above clones in southwestern Côte d'Ivoire. The results indicated that production systems that minimize the cost of latex harvesting admittedly resulted in losses of rubber yield per hectare per year from 1 to 37%, but improved the yield per tree per tapping as well as the productivity of the tapper from 20 to 46%, in year. Moreover, these systems contributed to the improvement of the vegetative growth of trees and kept the rate of dry trees in low level (less than 7%). Furthermore, these systems also helped to reduce the cost of tapping labor from 1 to 50%, as well as operating costs from 2 to 47%, in comparison with European Scientific Journal October 2018 edition Vol.14, No.30 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 191 the standard tapping (d3). Finally, in the context of a shortage of tapping labor, these systems help increase the farmer’s profit margin from 26% to 113%, as well as the tapper’s income from 26% to 89%. Therefore, it appears that the use of low frequency harvesting system with the appropriate stimulants appears as a solution to minimize latex harvesting cost and unavailability of harvesters in rubber cultivation.